An Impact Analysis of Interest Rates and Changes of Interest Rates on Stock Price and Changes on Stock Price . - Koperunthevy, K.; Vijayarani, K. (Sri Sai Ram Institute of Management Studies, 2012)
The macro economic variables have strong influence on stock market activities. Study attempts to identify the impact of interest rates and changes of interest rates on stock prices with a monthly observation from January 2005 to December 2011 in Sri Lanka. The ADF Unit Root test and Variance Inflation Factor (VIF) supported for the regression analysis. The regression results suggest that interest rate variation 44% on stock price and changes of interest rates variation 9% on changes of stock price. The F values are significant at 1% and 5% levels. Therefore, the interest rate influence on stock prices.
Keywords: Repo rate; Treasury bill rate; Fixed deposit rate; ASPI; Sri Lanka